A phase 1b trial of selinexor, a first-in-class selective inhibitor of nuclear export (SINE), in combination with doxorubicin in patients with advanced soft tissue sarcomas (STS). (February 2021) - Lewin, Jeremy; Malone, Eoghan; Al-Ezzi, Esmail; Fasih, Samir; Pedersen, Pernille; Accardi, Sarah; Gupta, Abha; Abdul Razak, Albiruni
Abstract: Background: Selinexor is a first-in-class selective inhibitor of nuclear export (SINE) compound with single-agent activity in soft tissue sarcoma (STS). The study's aim was to determine the safety and efficacy of selinexor in combination with doxorubicin in patients with locally advanced/metastatic STS. Methods: This phase 1b study used a mTPI design. Patients received selinexor at either 60 or 80 mg weekly PO plus doxorubicin (75 mg/m 2 IV q21 days). Patients with clinical benefit (defined as ≥stable disease via RECIST 1.1) after six cycles of combination treatment received maintenance selinexor until disease progression or unacceptable toxicity. Disease assessments were conducted every two cycles. Pharmacokinetic data were collected on the first three patients per dose level. Results: Twenty-five patients were enrolled (20 female, ECOG 0/1: 13/12, median age 57 years [range 21–74]). Disease subtypes included leiomyosarcoma (n = 6), malignant peripheral nerve sheath tumour (n = 3) and other sarcomas (n = 16). Three (12%) and 22 (88%) patients were treated at 60 mg and 80 mg of selinexor, respectively. The most common ≥G3 drug-related adverse events (AEs) were haematological, including neutropenia (56%), febrile neutropenia (28%) and anaemia (24%). There were four dose-limiting toxicities (febrile neutropenia (x2), vomiting, fatigue) all at the 80 mg dose level. There was one death secondary to heart failure. Of the 24 evaluable patients, 5 (21%) had a partial response and 15 (63%) had SD as best response. The estimated median progression-free survival (PFS) and overall survival (OS) were 5.5 (95% CI:4.1–5.7) and 10.5 (95% CI:7.5–14) months. Conclusion: In a heterogeneous group of patients with locally advanced/metastatic STS, the combination of selinexor and doxorubicin fulfilled the prespecified boundary for tolerability. Highlights: Study of patients with soft tissue sarcoma (STS) using a combination of selinexor and doxorubicin. Combination was tolerable with predominantly haematological and gastrointestinal (GI) adverse events. 21% of patients had a partial response and 63% had stable disease (SD) as best response.